Selected plays of Arthur Laurents - Laurents, Arthur (Back Stage Books, an imprint of Watson-Guptill Publications, 2004)
If he had done nothing more than write the book for the musicals West Side Story and Gypsy, Arthur Laurents would be assured a place in the pantheon of American theater. But he has done much more, including directing, screenwriting, and playwriting. Here, for the first time, is an anthology of seven of Laurents' most acclaimed and challenging plays. It begins with Home of the Brave, the play that launched Laurents' career. This wartime drama known for its frank treatment of anti-Semitism and war trauma remains as potent today as it was when it opened on Broadway in 1945. The anthology continues through some of Laurents' most recent work, including 2 Lives, a witty, frequently poignant portrait of an elderly gay couple confronting mortality and coming to terms with their lives. Also included are The Enclave, Jolson Sings Again, My Good Name, Closing Bell, and Attacks on the Heart. Spanning nearly 60 years and covering a wide variety of topical and emotional terrain, this is an important book from an American theater legend. --Publisher description.